Demographic Explosion in the Sahel : Dividend or Burden? - World Bank Group (World Bank, Washington, DC, 2018)
Like many other countries in Sub-Saharan Africa, this sub-group of West and Central African countries has experienced relatively fast drops in mortality but persistently high levels of fertility, which implies continued high rates of population growth, which represent an important challenge to development prospects. At the micro level, families will face challenges to ensure that their children are well educated, nourished and healthy. At the macro level, governments will face enormous pressures to keep pace with additional cohorts of schoolchildren to educate, new entrants into the labor market, and a general rise in demand for health and social services that will outstrip the capacity of fragile systems in these countries. The authorities in thesecountries have an important window of opportunity for addressing demographic issues systematically as part of their broader economic development plans and long-term vision documents.